A novel inverse dynamic model for 3-DoF delta robots. (May 2022) - Falezza, Fabio; Vesentini, Federico; Di Flumeri, Alessandro; Leopardi, Luca; Fiori, Gianni; Mistrorigo, Gianfrancesco; Muradore, Riccardo
Abstract: Delta Robots belong to a class of parallel robots widely used in industrial production processes, mostly for pick-and-place operations. The most relevant characteristics are the high speed and the extremely favorable ratio between the maximum payload and the weight of the robot itself. A reliable dynamic model is needed to implement torque controllers that reduce unnecessary high accelerations and so mechanical vibrations. The state-of-art inverse dynamic models exploit simplifications in order to facilitate the derivation of the equations of motion and their implementation. In this work, a novel and more rigorous inverse dynamic model is presented which does not rely on simplifications of the kinematic structure. The model has been validated comparing its estimations with real torques data collected moving a Delta Robot D3-1200 by SIPRO Srl; the computational complexity of the algorithm has also been investigated.